Non‐linear power oscillation damping controllers for doubly fed induction generators in wind farms. Issue 2 (1st March 2013) - Elkington, Katherine; Ghandhari, Mehrdad
Abstract : This study presents two methods for designing power oscillation damping (POD) controllers for wind farms comprising doubly fed induction generators (DFIGs). The first is the residue method, which uses linear feedback. The second method uses a non‐linear signal as feedback. Here linear matrix inequalities (LMIs) and regional pole placement are used to determine the feedback gains for multiple wind farms simultaneously so that the power system satisfies a minimum damping ratio. The impact of the designed POD controllers in wind farms is demonstrated in a test power system. Modal analysis is used to design controllers using both the residue and LMI methods, and dynamic simulations are used to demonstrate the contribution of the wind farms to power system damping. Numerical simulations show that DFIGs, such as those found in wind farms, are capable of damping oscillations, and also illustrate the effectiveness of using non‐linear feedback controllers.